(3fSeI GdSMQ aj PcQ ef JTjY hnTnYQs - (3Gdjefj, GdUfYGfj, GdRjOj, GdMSjfj, jhSa Hf jMji Hf GdMSjf Hf GdeDjO eMeO Hf GdbGSe, J (B1121 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3bGd eDdag (B...(3efP QRbJ GdYRjeI haGQbJ GdJeGe , hLGQjJ HGdacQI GdSdjeI ZdjdGJ (B...s
(3BNQgG (B:s
...(3hWNGQSJGf HaJM GdWGA GdegedI hGdNGA GdeYLeI hGdCda hGdQGA hGdSjf GdegedI GdSGcfI hGdJGA GdeKfGI GdahbjI HYOgG Cda Ke fhf (B... (3hMSHfG Gddgs
(3efbhd Yf fSNI HNW GdeDda (B- (3aj Chdg agQSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3gOjI GdYGQajf , ddHZOGOj (B2/568s
(3EjVGM Gdecfhf (B2/645s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJGQjNs